Overweight/Obesity among adult (20 years old and over) residents of urban Barangays anchoring the Iloilo River. - Cueva, Lorelei; Grino, Lowela May
This study aimed to determine the prevalence of overweight/obesity among adult (20 years old and over) residents of urban barangays anchoring the Iloilo River.